(untitled) (Research, Society and Development, 2021)
Otitis is a common condition among dogs and requires appropriate treatment. Given the importance of the otitis externa and the use of products to combat this condition, this study evaluated the in vitro antimicrobial abilities of six commercial ear cleaners solutions (EC1 to EC6) and solutions of 3% boric acid, 3% lactic acid, 0.11% salicylic acid, 0.5% chlorhexidine, and 3% propylene glycol against Staphylococcus spp., Pseudomonas spp., Proteus spp., and Malassezia spp. The in vitro diffusion capacity in synthetic cerumen was also assessed. Dogs with clinical signs of otitis externa were selected and samples were collected from the external ear canals. The microbiological study was performed to identify the microorganisms from samples collected and the microorganisms isolated were used in the study. One ceruminolytic for human use and five commercial solutions used for canine ear cleaning were selected based on the diversity of the components used in each formula. The results show a variation of antimicrobial activity and diffusion capacity ear cleaners and its compounds. Lactic acid, chlorhexidine, EC1, EC2, EC4, and EC5 showed the best results for microbiological growth inhibition; boric acid, salicylic acid, propylene glycol and EC6 had little or no effect on microorganism growth. The ECs tested demonstrated diffusion capacity using the SSC. EC1 was the solution with the most significant responses, both as an antimicrobial agent and with regards to diffusion capacity. Among the commercial veterinary products tested, EC4 was found to have the best results.